Decision Making Under Fuzzy Environment - Temizkan, Hasan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
High competition between universities has been increasing over the years, and stimulates higher education institutions to attain higher positions in the ranking list. Ranking is an important performance indicator of university status evaluation, and therefore plays an essential role in students’ university selection. In this thesis, analytic hierarchy process (AHP) and fuzzy analytic hierarchy process (FAHP) are applied for the comparison and ranking of performances of five UK universities, according to four criteria. The criteria used for the evaluation of universities’ performances are teaching, research, citations, and international outlook. The comparison matrix is used to compare criteria as well as alternatives with respect to each criterion. Consistency index and consistency ratio are calculated by using eigenvalues to check the consistency of comparison matrix and by obtaining the final priorities, ranking is possible with AHP. Eigenvalues are also calculated to check the consistency for FAHP as well as eigenvectors are calculated for ranking process. Besides these, by the calculation of coefficient of variation for all alternatives, it becomes possible to rank the universities in prioritized order with FAHP. Keywords: Ranking, Analytic Hierarchy Process (AHP); Fuzzy Analytic Hierarchy Process (FAHP); ranking; consistency; eigenvalue; eigenvector; coefficient of variation.

ÖZ: Üniversiteler arasındaki yüksek rekabet yıllar geçtikçe artmakta ve yüksek öğretim kurumlarını sıralama listesinde daha üst sıralara ulaşmaya teşvik etmektedir. Sıralama, üniversite durum değerlendirmesinin önemli bir performans göstergesidir ve bu nedenle öğrencilerin üniversite seçiminde önemli bir rol oynar. Bu tezde, Birleşik Krallık'taki beş üniversitenin performanslarının dört kritere göre karşılaştırılması ve sıralanması için analitik hiyerarşi süreci (AHP) ve bulanık analitik hiyerarşi süreci (FAHP) uygulanmıştır. Üniversitelerin performanslarının değerlendirilmesi için kullanılan kriterler öğretim, araştırma, alıntılar ve uluslararası görünümdür. Karşılaştırma matrisi, kriterleri ve her bir kritere göre alternatifleri karşılaştırmak için kullanılır. Karşılaştırma matrisinin tutarlılığını kontrol etmek için özdeğerler kullanılarak tutarlılık indeksi ve tutarlılık oranı hesaplanır ve nihai öncelikler elde edilerek AHP ile sıralama yapılabilir. Özdeğerler ayrıca FAHP için tutarlılığı kontrol etmek için hesaplanır ve ayrıca sıralama işlemi için özvektörler hesaplanır. Bunların yanı sıra tüm alternatifler için varyasyon katsayısı hesaplanarak FAHP ile üniversiteleri öncelik sırasına göre sıralamak mümkün hale geliyor. Anahtar Kelimeler: Sıralama, Analitik Hiyerarşi Süreci (AHP); Bulanık Analitik Hiyerarşi Süreci (FAHP); sıralama; tutarlılık; özdeğer; özvektör; varyasyon katsayısı.
Doctor of Philosophy in Applied Mathematics and Computer Science. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2021. Supervisor: Prof. Dr. Rashad Aliyev.
Keywords: Mathematics; Applied Mathematics and Computer Science; Fuzzy Logic--Fuzzy Mathematics; Ranking; Analytic Hierarchy Process (AHP); Fuzzy Analytic Hierarchy Process (FAHP); ranking; consistency; eigenvalue; eigenvector; coefficient of variation